2003
DOI: 10.1161/01.cir.0000053559.46158.ad
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Glycoprotein IIb/IIIa Antagonists and Aspirin on the Release of Soluble CD40 Ligand During Platelet Stimulation

Abstract: Background-Glycoprotein (GP) IIb/IIIa antagonists inhibit platelet aggregation, an activity attributed to the clinical benefits of these drugs in settings that involve acute coronary thrombosis. However, platelet activation and subsequent aggregation are now known to cause the release of a soluble form of CD40 ligand (sCD40L), a prothrombotic and proinflammatory protein with GP IIb/IIIa binding activity and an established role in atherosclerotic lesion progression. The present study was designed to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
3
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 35 publications
9
108
3
6
Order By: Relevance
“…Moreover, high levels of sCD40L correlate with cardiovascular events in patients with unstable coronary syndromes (13,16 -18). Glycoprotein (GP) IIb/ IIIa inhibitors may lower the level of platelet activation in vitro and the level of sCD40L released from platelets upon activation (19,20). A recent report from our group has demonstrated that the use of a GPIIb/ IIIa inhibitor in combination with an embolic protection device (EPD) during renal artery stenting may improve renal function after the revascularization procedure (21).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high levels of sCD40L correlate with cardiovascular events in patients with unstable coronary syndromes (13,16 -18). Glycoprotein (GP) IIb/ IIIa inhibitors may lower the level of platelet activation in vitro and the level of sCD40L released from platelets upon activation (19,20). A recent report from our group has demonstrated that the use of a GPIIb/ IIIa inhibitor in combination with an embolic protection device (EPD) during renal artery stenting may improve renal function after the revascularization procedure (21).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the characterisation of MMP-2, MMP-9 was identified to be an inhibitor of platelet aggregation suggesting that the MMP-9/MMP-2-dependent bioregulatory system might be involved in platelet-platelet and plateletvessel wall interactions (17). Moreover, platelet adhesion via glycoprotein (GP) IIb/IIIa upregulates CD40L and P-selectin (CD62P) surface exposure leading to the assumption, that clinical benefits of GP IIb/IIIa antagonists in addition to the inhibition of thrombosis by blocking platelet aggregation also involve the inhibition of inflammation and thrombosis via blockade of CD40L release (18,19). While molecular interactions of leukocytes with activated endothelial cells are critical for the defense against microbial invasion and immune trafficking, platelets also contribute to leukocyte targeting-and regulated accumulation (20)(21)(22).…”
mentioning
confidence: 99%
“…a variety of disease states characterized by endothelial activation [13] and activation of adaptive immune cells [14,15], including acute coronary syndromes [16][17][18][19], cerebral ischemia [20,21], pre-eclampsia [22], inflammatory bowel disease [23], and Kawasaki's disease [24].…”
mentioning
confidence: 99%